THE DIFFERENCES IN STOCK PORTFOLIO PERFORMANCE BEFORE AND DURING THE COVID-19 PANDEMIC: STUDY ON THE LQ-45 INDEX AND THE JAKARTA ISLAMIC INDEX - Utami, Eristy M.; Afrian, Irfan; Rosano, Aldora A.; Nabilqis, Maritha A.; Fahrenthy, Reinsya E.; Florensita, Mega C. (CENTRAL ASIA AND THE CAUCASUS, 2022)
The purpose of this research was determine differences in stock portfolio performance before and during the pandemic on the LQ-45 and JII indexes. The performance measurement method used is the Sharpe, Treynor, and Jensen index. The population of this research is all shares of LQ-45 and JII companies listed on the Indonesia Stock Exchange during the period of a year before the pandemic, there are March 2019-February 2020, and a year during the pandemic, there are April 2020- March 2021. Then a sample of 34 companies was obtained for the LQ-45 and 19 companies for the JII index. The results of the analysis show that by using this method approach, there is no difference in portfolio performance before and during the covid-19 pandemic, both on the LQ-45 index and on the JII index.